## Trending News

Promoted

### 1 Answer

Relevance

- Anonymous10 years agoFavorite Answer
Do you mean y = asin[k(x - c)] + d?

y = asin[k(x - c)] + d

Subtract both sides by d:

y - d = asin[k(x - c)]

Divide both sides by a:

sin[k(x - c)] = (y - d)/a

Then, set both sides by the inverse of sine.

k(x - c) = arcsin((y - d)/a)

Divide both sides by k:

x - c = arcsin((y - d)/a)/k

Finally, add both sides by c:

x = arcsin((y - d)/a)/k + c

I hope this helps!

Source(s): Knowledge

Still have questions? Get your answers by asking now.